Visualization software for computer graphics concepts: 3D transformation - Maskil Masjuri (Nanyang Technological University, 2022)
Computer graphics is a popular course being taught in schools. Many components make up the entirety of the subject, with 3D transformation being one of the fundamental concepts of computer graphics. Students require a solid understanding of this concept to be able to fully appreciate other aspects of the discipline. However, the teaching of 3D transformation is difficult. Conventional methods of teaching using diagrams and mathematical formulae are not always effective. Studies have explored the use of interactive methods of learning through the utilisation of existing 3D modelling software. Although they have been proven somewhat successful, there are drawbacks. Using this type of software requires the students to have prior experience, or else additional training would be necessary. This study investigates the viability of developing software that can be used as a tool in aiding the teaching of computer graphics concepts, with a focus on 3D transformation. OpenSceneGraph, a graphics rendering toolkit was used to develop the prototype. The software is an interactive application that visualises concepts of linear transformation, fixed and Euler angles, and quaternion representation.